Can Justice System Interventions Prevent Intimate Partner Homicide? An Analysis of Rates of Help Seeking Prior to Fatality. Issue 17 (September 2021) - Koppa, Vijetha; Messing, Jill Theresa
When women are killed, they are more likely to be killed by an intimate partner than anyone else, and a substantial number of women who are killed by an intimate were abused by that intimate partner before their death. The proportion of men killed by an intimate partner is much lower and prior research indicates that male intimate partner homicide victims are likely to abuse their partners prior to their deaths. However, limited research has examined the criminal and civil justice help seeking of intimate partner homicide victims. This study examines administrative data from one large urban police jurisdiction to understand rates of help seeking by homicide victims in the 1 to 3 years prior to the homicide. Over 4 years (2010-2014), 197 women and 776 men were killed. The proportion of women killed by an intimate or ex-intimate partner was 39.6%, and the proportion of men killed by an intimate or ex-intimate partner was 3.9%. Police had been in contact with the victim of intimate partner femicides for a domestic violence complaint in 91% of cases in the 3 years prior to the femicide (44.9% resulted in arrest), with an average of 6.2 visits per contacted victim. Among male intimate partner homicide victims, 73.3% had been the complainant on a domestic violence case (38.1% resulted in arrest). Few (<10%) victims sought protection orders before the homicide. Over the 3 years prior to their deaths, 36.7% of male homicide victims and 9.0% of femicide victims had been the suspect in a domestic violence case. Results indicate high rates of engagement of police officers with intimate partner homicide victims before their deaths, and highlight the opportunity for homicide prevention through integration of risk assessment (to identify high-risk cases) and enhanced criminal justice and social service interventions in high-risk cases.